2021
DOI: 10.3389/fpls.2021.698487
|View full text |Cite
|
Sign up to set email alerts
|

The Glycine-Rich Domain Protein GRDP2 Regulates Ovule Development via the Auxin Pathway in Arabidopsis

Abstract: The glycine-rich domain proteins (GRDP) have been functionally implicated in the cell wall structure, biotic, and abiotic stress responses. However, little is known about GRDP genes in female gametophyte development of Arabidopsis. This study shows that GRDP2, a GRDP, plays a crucial role in female gametophyte development. In GRDP2 overexpression lines, grdp2-3, the embryo sacs were arrested at FG1 and no nucleus stages. Furthermore, callose staining shows that cell plate formation during megasporogenesis is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is noteworthy that several genes involved in flora reproductive development and flowering time were also identified ( Table 3 ). GRDP2 encodes a novel glycine-rich domain protein that modulates flowering time and ovule development ( Ortega-Amaro et al, 2015 ; Czolpinska and Rurek, 2018 ; Wang et al, 2021b ), and was previously identified to be involved in environmental response in Arabidopsis ( Mangeon et al, 2010 ; Ortega-Amaro et al, 2015 ). BAM1 has been shown to regulate anther development in Arabidopsis ( Hord et al, 2006 ), and MS5 is known to be essential for male fertility in Arabidopsis and Brassica species ( Glover et al, 1998 ; Zeng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that several genes involved in flora reproductive development and flowering time were also identified ( Table 3 ). GRDP2 encodes a novel glycine-rich domain protein that modulates flowering time and ovule development ( Ortega-Amaro et al, 2015 ; Czolpinska and Rurek, 2018 ; Wang et al, 2021b ), and was previously identified to be involved in environmental response in Arabidopsis ( Mangeon et al, 2010 ; Ortega-Amaro et al, 2015 ). BAM1 has been shown to regulate anther development in Arabidopsis ( Hord et al, 2006 ), and MS5 is known to be essential for male fertility in Arabidopsis and Brassica species ( Glover et al, 1998 ; Zeng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, PPC1 exhibits a circadian-regulated expression pattern, is involved in light-regulated development via interaction with the COP9 signalosome subunit 5, and regulates the flowering transition in the photoperiod-dependent pathway [ 52 , 53 , 54 ]. AtGRDP2 also regulates female gametophyte development via the auxin pathway, and plants overexpressing it show early flowering [ 50 , 55 ]. Meanwhile, BES1 directly represses AtMYB56 , which positively regulates the quiescent center and cell division [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%